Application of cross section polishing and FE-SEM observation to tailings generated from flotation of ores - Okada, Takashi (2014)
Fine particles in tailings generated from the flotation of ores were observed. By using Field-emission scanning electron microscopy (FE-SEM), the fine particles were observed at submicron level with high resolution. For the cross section observation, the tailing samples were prepared by cross section polishing. With the combination of these techniques, we determined the distributions of the heavy metals and metalloids in the fine particles. As a result, when the particle surfaces were observed, the detection of Pb, Sb, Fe and/or As indicated that these elements coexist or separately exist in the 1−3 μm fine particles. In the cross section observation, the concentrations of Zn and Fe were found to be different in the particles.